2013
DOI: 10.1371/journal.pntd.0002199
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Exploring Barriers Related to Use of Footwear in Rural Highland Ethiopia: Implications for Neglected Tropical Disease Control

Abstract: BackgroundThe role of footwear in protection against a range of Neglected Tropical Diseases (NTDs) is gaining increasing attention. Better understanding of the behaviors that influence use of footwear will lead to improved ability to measure shoe use and will be important for those implementing footwear programs.Methodology/Principal FindingsUsing the PRECEDE-PROCEED model we assessed social, behavioral, environmental, educational and ecological needs influencing whether and when children wear shoes in a rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 30 publications
(32 reference statements)
7
57
0
Order By: Relevance
“…Looking at the donated shoe use by activity, children appear to have worn them most frequently as house shoes, for play, and for school 4). The data therefore do not show any significant social or attitudinal barriers to footwear use, as has been found in other settings (e.g., Ayode et al 2013). Our endline survey also found that 95% of the treated children had a favorable impression of the shoes.…”
Section: Difference-in-difference and Ancova Estimationsupporting
confidence: 80%
“…Looking at the donated shoe use by activity, children appear to have worn them most frequently as house shoes, for play, and for school 4). The data therefore do not show any significant social or attitudinal barriers to footwear use, as has been found in other settings (e.g., Ayode et al 2013). Our endline survey also found that 95% of the treated children had a favorable impression of the shoes.…”
Section: Difference-in-difference and Ancova Estimationsupporting
confidence: 80%
“…However, it should be noted that in the underprivileged communities there are several barriers to affecting positive change beyond the scope of simply providing education. One such issue is that the option for children to consistently wear shoes may be limited due to the lack of familial financial resources, meaning that people are unable to purchase more than one pair of shoes, and in some cases may not even be able to afford shoes for all their family members [ 47 , 48 ]. Similarly, we observed that most Orang Asli children walked and played barefooted.…”
Section: Discussionmentioning
confidence: 99%
“…Two issues may explain this: first, podoconiosis is a chronic disease primarily affecting the feet, so reverse causality is likely (when an individual first notices foot or leg swelling, he or she starts wearing shoes), and second, podoconiosis requires a long period of exposure, but assessment of current use of footwear does not reflect previous exposure [35] . Studies comparing podoconiosis patients with healthy controls have found that patients tend to wear footwear more than healthy controls to protect their legs from injury or to conceal the swelling in fear of stigma and discrimination [36] , [37] . Other studies have suggested that age at first footwear use would be a more precise indicator of protection than current footwear use [38] .…”
Section: Discussionmentioning
confidence: 99%